An exchangeable SIM probe for monitoring organellar dynamics of necrosis cells and intracellular water heterogeneity in kidney repair - Youbo Lai; Tengteng Zhang; Ling Huang; Andrey S. Klymchenko; Weiying Lin (Proceedings of the National Academy of Sciences, 2025)
Monitoring subcellular organelle dynamics in real time and precisely assessing membrane heterogeneity in living cells are very important for studying fundamental biological mechanisms and gaining a comprehensive understanding of cellular processes. However, there remains a shortage of effective tools for these purposes. Herein, we propose a strategy to develop the exchangeable water-sensing probeAPBD for time-lapse imaging of dynamics in cellular membrane-bound organelle morphology with structured illumination microscopy at the nanoscale. In this work, our results reveal mitochondria as the first organelle to undergo morphological changes through swelling, fission, and fusion in cell necrosis, leading to the rupture of the endoplasmic reticulum (ER) sheet adhered to the mitochondria. Meanwhile, the ER tubules are then reconstructed by stretching and fusion of autophagosomes. Moreover, APBD allows us to directly visualize spatially resolved distribution of biomembranes vs. water inside single mammalian cells. Our findings show that the renal ischemia–reperfusion injury (IRI) model results in the increased biomembrane to cytoplasmic water ratio in the tissue. This reveals intracellular water heterogeneity between the nucleus and the cytoplasm during the IRI process. Overall, this study presents a strategy for development of the molecular tools for cellular water heterogeneity and organelle dynamics.